Pengembangan Modul Berbasis Discovery Learning Terintegrasi Sains Pada Materi Kesetimbangan Kimia - Riska, Cut Safrida; Sutiani, Ani (ARKA INSTITUTE, 2022)
This study aims to determine the feasibility and student responses, from the development of a Discovery Learning- Based Module that is integrated with scientific literacy. The subject of this research is a module based on the Discovery Learning learning model which is integrated with scientific literacy. The object of this research is the material of chemical equilibrium. This type of research is a development that refers to the ADDIE model. This study uses non-test instruments, non-test instruments used in the form of Validation Sheets that have met the BSNP standards, namely aspects of the feasibility of content, presentation, language and graphics by the validator and student response questionnaire sheets with a scale of five categories. The results of the feasibility validation show that the development of discovery learning-based modules is integrated with scientific literacy in chemical equilibrium material. The average percentage of media expert validators' assessments on content feasibility is 87.32%, presentation feasibility is 88%, language eligibility is 85.28%. And for the average percentage of media assessment on the feasibility of graphics is 93.50% and language feasibility is 88.86%. And on the results of the average percentage of student responses to the attractiveness aspect of 89.6%, the material aspect of 90.6%, the language aspect of 92.6%.